Law Enforcement Against Unreported Fishing: What Does Beyond the Catch Record? - Rachma Indriyani; Asmar Abdul Rahim; Ruzita Azmi (Sriwijaya Law Review, 2022)
Transparency is significant in highly migratory fisheries. The reliability of the catch data is essential for decisions of internationally agreed targets. Nevertheless, the data accuracy will much depend on each state's performance. Focusing on unreported catches of migratory fish, this study highlights the Thunnus Macoyyi (Southern Bluefin Tuna) fishing in Indonesia, as this fish species had experienced for being the limelight of unreported fishing allegations. The main objective is to reveal what are the difficulties that Indonesia is facing on its responsibility to maintain the accuracy of the catch record. Accordingly, the study examines two points by applying the pure legal method and doctrinal approach. Firstly, the international legal framework towards unreported fishing by analysing three main instruments such as the UNCLOS 1982, the UNFSA 1995, and the CCSBT policies. Secondly, it examines Indonesia law enforcement as a State party of regional fisheries organisation. It argues that the international authority could not be completely extended to a State's domestic fishing area. Thus, it gives more discretion to the national law to enforce compliance. Lesson learned from the case study of Indonesia's southern bluefin tuna contributes to unreported fishing literature and allows us to expose the legal gap remained in managing highly migratory fish stocks.